Análise de virulência e ação de antimicrobianos terapêuticos e potenciais antimicrobianos em células planctônicas e em biofilme de Escherichia coli enteroagregativa: um estudo in vitro e in vivo - Guerrieri, Caroline Gastaldi (2022)
Enteroaggregative Escherichia coli (EAEC) is characterized by heterogeneity of potential virulence factors and biofilm formation. It can be classified as typical (tEAEC) and atypical (aEAEC) based on the presence of the AggR regulon, suggesting a higher virulence for tEAEC. As a result of its remarkable heterogeneity, its identification and determination of the susceptibility profile are not performed in the routine of laboratory diagnosis, and its treatment is done empirically. In addition, biofilm formation, which leads to the occurrence of persistent infections that may require antimicrobial therapy, confers resistance to antimicrobials and, in most cases, makes their eradication impossible. Therefore, the development of new therapeutic strategies for EAEC infections, mainly associated with biofilm formation, is sorely necessary. Phendione and its metallic derivatives (Ag-phendione and Cu-phendione) have shown effectiveness against several microorganisms, but so far their activity in E. coli isolates has not been investigated. Given the above, we aimed to analyze in vivo aspects of EAEC virulence and to analyze in vitro and in vivo the action of classic and new antimicrobials (phendione and its derivatives) on planktonic cells and EAEC biofilm. Regarding virulence analyses, we evaluated the survival of larvae after inoculation of the EAEC 042 wild-type and its AggR mutant. To evaluate the combination therapy with classic antimicrobials, the biofilm was formed in a peg-lid system, treated with combinations of antimicrobials from different therapeutic classes, and the inhibition and eradication potential of each combination was determined. We also analyzed the activity of phendione-derived compounds for EAEC in the planktonic form by determining the minimum inhibitory concentration (MIC) and evaluating combinations of compounds with antimicrobials for resistant strains using checkerboard and time-kill methodologies. We also investigated the anti-biofilm activity of the compounds by determining the minimum biofilm inhibitory concentration (MBIC) and minimum biofilm eradication concentration (MBEC), in addition to other aspects such as the ability to inhibit the formation and disarticulate the mature biofilm and the possibility of using compounds associated with classic antimicrobials as a combined therapy to biofilm inhibition and eradication. Finally, we tested the treatment with Cu-phendione and Ag-phendione and their association with ampicillin in vivo in the G. mellonella model. Regarding the virulence of EAEC, we observed that the EAEC 042 mutant AggR strain showed a significant reduction in the mortality of inoculated larvae in relation to the wild-type strain, but its virulence was not completely lost. Combination therapy of classic antimicrobials in EAEC biofilms led to the eradication of 50% of the tested strains (2/4) in the ciprofloxacin-ampicillin and ciprofloxacin-tobramycin combinations. Phendione and its metal complexes showed high activity against EAEC strains in planktonic form with low MIC value, and, combining the metal complexes with antimicrobials by the checkerboard method, we observed an additive effect in most combinations. On the other hand, in time-kill experiments, the compounds showed synergism with both tetracycline and ampicillin. Regarding anti-biofilm activity, Cu-phendione showed the best result in the biofilm inhibition and eradication (68.6% - 24/35 strains), in the disarticulation of the mature biofilm (IC50 = 1.87 μM) and the inhibition of biofilm formation, mainly after six hours of incubation. Evaluating combination therapy in biofilms, we observed biofilm eradication of all strains (4/4) in combinations of Cu-phendione with cefoxitin, tobramycin, tetracycline, and ciprofloxacin, and in combinations of Ag-phendione with tobramycin and ciprofloxacin. Furthermore, the combination of ampicillin with Ag-phendione significantly increased the survival of G. mellonella larvae when compared to ampicillin administered alone. In conclusion, the results obtained here demonstrate that the in vivo virulence of EAEC seems to be related to the AggR regulon, but not exclusively. Regarding the treatment strategies for EAEC infections associated with biofilm formation, despite the combination therapy with two classic antimicrobials having presented better results than the treatment with antimicrobials alone, analyzed in a previous study, the phendione-derived compounds were more promising, especially for its ability to eradicate the biofilm either alone or in association with antimicrobials.